2014
DOI: 10.1002/adhm.201400299
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Reactive Oxygen Species (ROS)‐Responsive Nanoparticles as Superior Drug Delivery Vehicles

Abstract: A novel reactive oxygen species (ROS)-responsive nanoplatform can be successfully manufactured from a ROS-triggerable β-cyclodextrin material. Extensive in vitro and in vivo studies validate that this nanoscaled system may serve as a new drug delivery vehicle with well-defined ROS-sensitivity and superior biocompatibility. This nanocarrier can be used for ROS-triggered transport of diverse therapeutics and imaging agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 38 publications
4
91
0
Order By: Relevance
“…This was mainly resulted from hydrolysis of Ac2-26 in the harsh environment of the gastrointestinal tract, which is a major challenge for oral delivery of peptides/proteins. [30,32] More importantly, our comprehensive in vitro and in vivo studies have revealed good safety profile for nanocarriers based on OxbCD. Our previous studies substantiated that NPs based on a ROS-responsive material OxbCD can be selectively hydrolyzed under inflammatory conditions with overexpressed ROS, while they are stable in the stomach.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This was mainly resulted from hydrolysis of Ac2-26 in the harsh environment of the gastrointestinal tract, which is a major challenge for oral delivery of peptides/proteins. [30,32] More importantly, our comprehensive in vitro and in vivo studies have revealed good safety profile for nanocarriers based on OxbCD. Our previous studies substantiated that NPs based on a ROS-responsive material OxbCD can be selectively hydrolyzed under inflammatory conditions with overexpressed ROS, while they are stable in the stomach.…”
Section: Discussionmentioning
confidence: 94%
“…[26][27][28] While currently developed NPs are able to protect the loaded biologic drugs from hydrolysis in the gut, low bioavailability is generally observed due to insufficient and uncontrolled release at diseased sites, thereby leading to undesirable efficacies. Based on our existing expertise in ROS-responsive nanovehicles and the potency of Ac2-26, [30][31][32][33][34] we developed an Ac2-26 peptidecontaining nanotherapy for site-specific delivery to the inflamed colon in IBD. [26] As well documented, oxidative stress, characterized by overproduced reactive oxygen species (ROS), is closely related to the pathogenesis of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…370 ROS species such as hydroxyl radicals (HO • ) and hydrogen peroxide (H 2 O 2 ) are produced in different parts of the cell as a by-product of electron transfer reactions. 370 In one study well-defined ROS-sensitive β-CD-based smart DDSs 371 were prepared by incorporation of oxidation-responsive boronic ester units into the structure. Cytocompatible micelles containing polypropylene sulfide (PPS) were developed to form a ROS-triggered drug release system taking advantage of the increased hydrophilicity of the PPS core that was disassembled after oxidation by the ROS rich environment.…”
Section: Different Stimuli-responsive Mnpsmentioning
confidence: 99%
“…ROS are known to be elevated during ischemia and to remain elevated during the first 24 h post reperfusion, the period which represents the most relevant and effective clinical time point for treatment of MI. [19] Furthermore, the unique ROS-responsive nanoparticles described here could be utilized for in vivo molecular imaging of ROS levels in order to diagnose ischemic conditions or to validate anti-oxidative treatment strategies following I/R injury. Thus, a ROS-responsive nanoparticle drug-delivery system offers a promising approach for the treatment of various I/R injuries such as stroke and renal infarction.…”
mentioning
confidence: 99%
“…[13] Increased production of ROS occurs in ischemia/reperfusion independent of the organ involved. [19] Currently, ROS levels are generally measured and monitored either in vitro using isolated cardiac myocytes or ex vivo using a Langendorff perfused heart. Furthermore, ROS generation has been described in several pathological processes such as cancer, diabetes, and aging, as well as inflammation-mediated diseases such as rheumatoid arthritis.…”
mentioning
confidence: 99%